A simple effectiveness model for heat wheels - Seo, Jang-Won; Lee, Dae-Young; Kim, Dong-Seon (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Rotary heat exchangers or heat wheels are popularly used for heat recovery in many industrial and domestic applications. In this study, a simple effectiveness model is developed for general use in the field. Firstly, approximate solution is obtained for the governing equations of a periodic-flow heat exchanger by assuming similarity with a steady-state heat exchanger and then used to derive an effectiveness correlation. The correlation is compared with a widely accepted reference in the literature and found to give a maximum error of 5% in the investigated ranges. Simple empirical correlations are also provided for practical use in the field. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: SENSIBLE EFFECTIVENESS; ENERGY RECOVERY; AIR